Development of digital marketing models for MSMEs to improve the community's economy - Nur Laila Yuliani; Muhamad Rifki Efendi; Ocky Sanjaya; Muhamad Izdad Fuadi; Ahmad Faisal; Advent Rainaldy (Community Empowerment, 2022)
The main objective of the Semaken Hamlet, Pucung Rejo Village Integrated Community Service program is to provide innovative marketing models using digital media. This should allow for increased product marketing. Socialization, training, and mentoring are the three methods used to provide this program. As a result of this program, MSME actors now have accounts on the marketplace as well as social media platforms such as Instagram and Facebook, which they can effectively manage. Furthermore, each MSME actor has a product brand or logo and is familiar with financial reports that present information about MSME performance and are useful for making business decisions.